Zamrożenie nakładów i dyskonto efektów w nowej metodyce określania efektywności przedsięwzięć inwestycyjnych - Zapart, Maria (Wydział Prawa i Administracji UAM, 1977)
This article is an attempt at evaluating the new methodology for measuring cost effectiveness of investment project, from the point of view of its correctness in both substance and methodology. In the work it has been attempted to answer the question whether, and how much, investment freezing and cost effectiveness discounting are taken into acount in the present formulas for figuring effectiveness indicators. The present cost effectiveness formulas are presented and discussed. Also discussed is the economic sense of using investment freezing and cost effectiveness discounting. The author has pointed to the important differences in the functions attributed to these economic instruments in the new investment effectiveness methodology. The conclusion of the author is supported by examples annexed to the article, in which the level of cost effectiveness is estimated according to the instructions, as well as by taking into account investment freezing.
Investment Freezing and Cost Effectiveness Discounting in the New Methodology of Investment Appraisal